Inpatient mortality and associated clinical factors among people living with HIV with cryptococcal meningitis in Uganda: A retrospective cohort study - Joshua Kitimbo; Esther Buregyeya; Geofrey Mutole; John Paul Ibanda; Joseph Tumwine; Noah Kiwanuka; Thomas Buyinza (PLoS ONE, 2026)
Introduction Cryptococcal meningitis remains a leading cause of HIV-related mortality in sub-Saharan Africa despite expanded antiretroviral therapy coverage. Evidence on the burden of disease and inpatient mortality among people living with HIV (PLHIV) in routine care settings in Uganda remains limited. This study assessed the proportion of cryptococcal meningitis among HIV-related admissions and examined clinical factors associated with inpatient mortality. Methods We conducted a retrospective cohort study of adult PLHIV admitted with cryptococcal meningitis between 1 st /01/2017–31 st /12/2022 at a national referral hospital in Uganda. Diagnosis was based on cerebrospinal fluid cryptococcal antigen or India ink positivity. Data were abstracted from medical records and analysed using descriptive statistics and multivariable logistic regression to identify factors associated with inpatient mortality. Specific antifungal treatment regimens were not consistently documented and could not be analysed. Results Of 3,042 HIV-related admissions, cryptococcal meningitis accounted for 21.4% (650/3,042). Medical records for 634 patients were analysed, among whom 39.3% (249/634) died during hospitalization. Factors independently associated with higher odds of inpatient mortality included convulsions, headache, vomiting, cryptococcal meningitis–associated immune reconstitution inflammatory syndrome, concurrent opportunistic infections, chronic kidney disease, anaemia, and severe immunosuppression (low CD4 cell count). Longer duration of hospitalization (≥7 days) and symptom duration of one to two weeks before admission were associated with lower odds of mortality. Conclusion Cryptococcal meningitis continues to account for a substantial proportion of HIV-related hospital admissions and inpatient deaths in Uganda. Mortality is associated with identifiable clinical and health-system factors, underscoring the need for early diagnosis, risk stratification, and optimized inpatient management for PLHIV with cryptococcal meningitis in resource-limited settings.